2019
DOI: 10.1016/j.str.2018.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Calcarisporiella thermophila Hsp104 Disaggregase that Antagonizes Diverse Proteotoxic Misfolding Events

Abstract: Highlights d The dynamic assembly shows varying tunnel width, helical rise, and domain orientation d The N-terminal domain and C-terminal tail are not required for CtHsp104 hexamerization d CtHsp104 rescues TDP-43, polyGlu and a-Syn toxicity in yeast and is well tolerated d CtHsp104 confers thermotolerance to yeast suggesting collaboration with Hsp70/Hsp40

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 70 publications
2
46
0
Order By: Relevance
“…Indeed, we reported that an Hsp104 homolog from the thermophilic fungus Calcarisporiella thermophila antagonizes toxicity of TDP-43, αSyn, and polyglutamine in yeast without apparent toxic off-target effects [27]. These findings support our hypothesis that natural Hsp104 homologs may have therapeutically beneficial properties.…”
Section: Introductionsupporting
confidence: 82%
See 4 more Smart Citations
“…Indeed, we reported that an Hsp104 homolog from the thermophilic fungus Calcarisporiella thermophila antagonizes toxicity of TDP-43, αSyn, and polyglutamine in yeast without apparent toxic off-target effects [27]. These findings support our hypothesis that natural Hsp104 homologs may have therapeutically beneficial properties.…”
Section: Introductionsupporting
confidence: 82%
“…Next, we tested the activity of several Hsp104 homologs (ScHsp104, CtHsp104, TtHsp104, AtHsp104, and MtHsp104) against an ordered amyloid substrate, semen-derived enhancer of viral infection (SEVI) [69]. As previously reported [27,53], all Hsp104 homologs tested rapidly remodeled SEVI fibrils ( Figure S8A). Electron microscopy revealed that Hsp104 homologs remodeled SEVI fibrils into small, amorphous structures ( Figure S8B).…”
Section: Differential Suppression Of Proteotoxicity By Hsp104 Homologmentioning
confidence: 53%
See 3 more Smart Citations